Теоретико-правовий погляд на зміст об’єктивної сторони ст. 178 КУпАП: теза, антитеза, аргументи, демонстрація - Чишко, К. О.; Chyshko, K. O.; Чишко Катерина Олександрівна (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 2 (101), ч. 1. - С. 124-134, 2023)
Стаття побудована відповідно до елементів логічної операції «доведення», що включає в себе такі елементи: теза (не можна притягувати особу до адміністративної відповідальності за порушення ст. 178 КУпАП за розпивання пива, алкогольних, слабоалкогольних напоїв у громадських місцях); антитеза (положення про можливість притягнення особи до адміністративної відповідальності за порушення ст. 178 КУпАП за розпивання пива, алкогольних, слабоалкогольних напоїв у громадських місцях на підставі застосування аналогії закону); аргументи, що свідчать про хибність антитези; демонстрація, яка передбачає підтвердження тези.

The article is structured according to the elements of the logical operation of “proof”, which includes the following elements.Thesis: it is impossible to bring a person to administrative liability for violation of Article 178 of the Ukrainian Code of Administrative Offences for drinking beer, alcoholic or soft drinks in public places, if the person drinks these beverages, for example, in the apartment building entrance.Antithesis: administrative liability under Art. 178 of the Ukrainian Code of Administra-tive Offences is incurred for drinking beer, alcoholic or soft drinks in an entrance hall as a place prohibited by law, i.e. a public place, in accordance with para. 1, Part 1, Article 1 of the Law of Ukraine “On Measures to Prevent and Reduce the Use of Tobacco Products and Their Harmful Effects on Public Health”. The application of the Law regulating the state policy on prevention of smoking of tobacco products to regulate legal relations in the field of public order and public safety, in terms of drinking spirits in public places, is justified by using a specific method – analogy of law.Arguments: firstly, the presence of the phrase “other places prohibited by law” contained in part 1 of Article 178 of the Ukrainian Code of Administrative Offences does not indicate incompleteness of legal provisions, referring to part 3 of Art. 15-3 of the Law of Ukraine “On State Regulation of Production and Circulation of Ethyl Alcohol, Cognac and Fruit Alcohol, Alcoholic Beverages, Tobacco Products, Liquids Used in Electronic Cigarettes and Fuel”, and therefore there are no grounds for applying the analogy of the law; secondly, when establishing the objective side of Art. 187 of the Ukrainian Code of Administrative Offences in terms of drinking beer (except for non-alcoholic), alcoholic and soft drinks, it is necessary to distinguish between the categories of “public places” and “places prohibited by law”; thirdly, according to the current legislation, the application of the analogy of the law is the privilege of judges, while police officers do not have such powers, and the opposite may indicate a violation of the principle of legality of proceedings in cases of administrative offences.Presentation: the combination of the above arguments confirms the thesis that a person cannot be brought to administrative liability for violation of Article 178 of the Ukrainian Code of Administrative Offences.

Статья построена в соответствии с элементами логической операции «доказывания», включающей в себя следующие элементы: тезис (нельзя привлекать лицо к административной ответственности за нарушение ст. 178 КУоАП за распитие пива, алкогольных, слабоалкогольных напитков в общественных местах); антитеза (положение о возможности привлечения лица к административной ответственности за нарушение ст. 178 КУоАП за распитие пива, алкогольных, слабоалкогольных напитков в общественных местах на основании применения аналогии закона); аргументы, свидетельствующие о ошибочности антитезиса; демонстрация, подразумевающая подтверждение тезиса.
Theoretical and legal perspective on the content of theobjectivity of Article 178 of the Ukrainian Code of AdministrativeOffences: thesis, antithesis, arguments, presentation
Keywords: кваліфікація адміністративних правопорушень; аналогія права; аналогія закону; адміністративна відповідальність; громадське місце; qualification of administrative offence; analogy of law; analogy of legislation; administrative liability; public place; квалификация административных правонарушений; аналогия права; аналогия закона; административная ответственность; публичное место